PENERAPAN TIGA KOMPONEN LITERASI GAYA CREATIVE EDUCATION INDONESIA FOUNDATION (CREDO) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DI SD NEGERI PEGADINGAN 2 - Siti Della Sopyanti, - (2020)
This study tries to explain the process and results of applying the three components of literacy (phonology, phonics, alphabet knowledge) to the Credo style to elementary school students who have exceeded the initial reading learning period but still have difficulty in reading so that students experience difficulties when following other lessons. This study took respondents who sat between class three to class six. This research uses a qualitative method with a case study approach. However, in collecting data, researchers encountered obstacles due to Covid-19 which led to the implementation of Social and Physical Distancing, so that in the presentation of results and discussion researchers used primary data in the form of Pretest and interview results, then researchers used secondary data from source books as well as journals. relevant and prioritizing literature studies to confirm the results of this study. The conclusion drawn from this study is that all students assessed were not familiar with phonological concepts and skills in phonology. Students who are able to read sentences in general can read words, but students who are able to read words may not be able to read sentences. The ability to read words is not biased to determine the ability to write words. From the results obtained there were 54 students who had difficulty reading given treatment in the form of teaching the three structured and systematic literacy components that made it easier for students to read. As well as finding some interesting things such as: students who have high reading comprehension were not children who can read; students who are able to read (words / sentences) do not necessarily understand reading; students who are able to understand reading, some are able to read, some are not yet able to read.